Global innovation hotspots : innovation ecosystems and catching-up in developing countries: evidence from Shenzhen - Yin, Deyun; Raffo, Julio; Tang, Jie (World Intellectual Property Organization, 2022)
Based on international patent and scientific publication data, this report classifies Shenzhen's technological trajectory and catch-up process into three stages: 1) accessing advanced technology by participating in the Global Production Networks (GPNs) and Global Value Chains (GVCs), 2) accumulating technological knowledge and enhancing absorptive capability through imitation and 3) achieving indigenous innovation. We interpret this remarkable catch-up process from the perspective of 1) technological specialization, 2) the local innovation ecosystem and 3) its embeddedness into the Global Innovation Networks (GINs). The last part summarizes Shenzhen's policy lessons in fostering innovation-based economic growth in developing countries and areas.
Keywords: Patents.; Intellectual property.; Shenzhen (Guangdong Sheng, China : East); Innovation.